The Attitudes of the Students at the Palestinian Universities Towards, the Woman Work - Sai'd Mohammaed Ahmed Hamayel (My University, 2003)
The purpose of this study is to know the attitudes of the student’s at the Palestinian universities towards the woman work, according to the sex, the college, the motl1er's work, the father's work, the place of residence, the number of the family, the study level, and the academic average. To do this study samples are taken including (934) students (446 males, 488 females) forming the percent (7.71) of the society whose members were chosen randomly following the simple arbitrary samples. The researcher has made a questionnaire to measure the student's J attitudes, it consists of (73) paragraphs classified to five areas concerning i the subject ofthe woman’s work: family, psychological, economical, social, intellectual and administrative area. The questioner was showed to a panel of judges in addition to get l the validity. Reliability was calculated by using Corenbakh Alpha's method and the whole reliability was (0.86). And after dealing with the information, the information results were found: -The attitudes of the students of the Palestinian universities were positive and the Celsius percentage reached (63.6%). -There were significant differences in (α=0.05) in the attitudes of the students at the Palestinian universities towards the woman work according to the six varieties, the mother‘s work, the la1her's work, the place of residence, the number of the family, the study level and the academic average. No significant differences were found towards the students attitudes due to their colleges: -Adding the woman subject to the society among the obligatory requirements of the university concentrating on the family and social area. -Taking care with the working mothers and help them in psychological health in order to help them to take care of their children's psychological health.

هدفت هذه الرسالة إلى التعرف على اتجاهات طلبة الجامعات الفلسطينية نحو عمل المرأة, إضافة إلى تحديد الفروق في اتجاهات الطلبة في الجامعات الفلسطينية نحو عمل المرأة تبعاً لمتغيرات الجنس, الكلية, عمل الأم, عمل الأب, مكان الإقامة, عدد أفراد الأسرة, المستوى الدراسي, والمعدل الأكاديمي. لتحقيق ذلك أخذت عينة دراسية مكونة من (943) طالباص وطالبة منهم (446 ذكراً, 488 أنثى) ويشكلون ما نسبته (7.71) من أفراد مجتمع الدراسة والتي تم اختيار أفرادها اختياراً عشوائياً باتباع طريق العينة العشوائية. وقام الباحث ببناء استبانة لقياس الاتجاهات لدى الطلبة يتألف من (73) فقرة مصنفة إلى خمسة مجالات تتعلق بموضوع عمل المرأة هي: المجال الأسري والنفسي والاقتصادي والاجتماعي والفكري والإداري. وقد تم عرضها على هيئة محكمين إضافة إلى التحليل العاملي لاستخراج صدقها, وقد تم استخراج الثبات باستخدام معادلة كرونباخ- ألفا, حيث وصل الثبات الكلي للاستبانة (0.86). وبعد معالجة البيانات تم التوصل إلى النتائج الآتية: - أن اتجاهات طلبة الجامعات الفلسطينية نحو عمل المرأة إيجابية حيث وصلت النسبة المئوية للاستجابة على الاتجاهات الطلية إلى (65.61%). - وجود فروق ذات دلالة إحصائية عند مستوى الدلالة في اتجاهات طلبة الجامعات الفلسطينية نحو عمل المرأة تعزى لمتغيرات الجنس, وعمل الأم, وعمل الأب, ومكان الإقامة, وعدد أفراد الأسرة والمستوى الدراسي, والمعدل الأكاديمي. بينما لم تكن الفروق دالة إحصائيا تبعا لمتغير الكلية. وبناء على نتائج الدراسة, فقد أوصى الباحث بتوصيات من أهمها: - ضرورة إدخال مادة المرأة في المجتمع من ضمن متطلبات الجامعة الإجبارية مع التركز على المجال الأسري. - الاهتمام برعاية العاملات ومساعدتهـم على التمتع بالصحة النفسية الأمر الذي سيساعد على تهيئة الصحة النفسية المناسبة لأبنائهن.
اتجاهات طلبة الجامعات الفلسطينية نحو عمل المرأة